IMPLEMENTASI STRATEGI MARKET DEVELOPMENT DALAM MENGIKUTI PELELANGAN E-PROCUREMENT STUDI KASUS PADA CV PUTRA MULYA SEJAHTERA - Sutiono, Adi (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research would describe the decision process of market development strategy on CV Putra Mulya Sejahtera based on the theoretical framework of strategy formulation and strategy to follow the auction electronic (E-Procurement) as a form of market development strategy implementation. Research approach using qualitative case study approach. Data collection techniques include interviews, observations, questionnaires. Paired comparison method used to obtain the results of the weighting values. The analysis used the IFE and EFE matriks, SWOT, Matriks Grand Strategy and Internal-External Matriks QSPM. KeywordsÂ  : Implementation strategy, Market Development, E-Procurement, LPSE